IMPOLITENESS STRATEGIES USED ON ONLINE COMMENTS IN AN INDONESIAN FOOTBALL WEBSITE - Grace P. Wibowo; Esther Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2013)
This research investigates linguistic impoliteness used in online football comments through the examination of impoliteness strategies proposed by Jonathan Culpeper. It examines how impoliteness strategies are used on online comments and what strategy mostly used by Indonesian participants in Okezone, an Indonesian football website. The research uses descriptive qualitative method supported by quantitative data. First, the writer found that Indonesian participants mostly used positive impoliteness strategy to express their negative attitude on giving comments. Second, there are four out of five impoliteness strategies used by Indonesian participants. Withhold politeness strategy is excluded.